Direct and indirect contacts between cattle farms in north-west England - Brennan, Marnie L.; Kemp, R.; Christley, Robert M. (Elsevier, 2008)
Little is known regarding the types and frequencies of contact that exist between farms and which of these may act as pathogen transmission routes; however it is likely that farms demonstrate considerable heterogeneity in such contacts. In this cross-sectional study, we explored the direct and indirect contact types and frequencies that exist between cattle farms within a region, focusing on potential routes of pathogen transmission. The owners/managers of 56 farms located in a 10 km by 10 km study area in north-west England were administered an interview-based questionnaire between June and September 2005. Information was obtained relating to contact types and frequencies, including those involving animal movements, equipment sharing between farms and any contractors or companies visiting the farms.